The Preservation of the Whole and the Teleology of Nature in Late Medieval, Renaissance and Early Modern Debates on the Void - Manzo, Silvia (Journal of Early Modern Studies.)
This study shows that an important number of late medieval, Renaissance and early modern authors postulated the same teleological principle in order to argue both for and against the existence of the vacuum. That postulate, which I call the "principle of subordination," holds that in order to preserve the good of nature, the particular and specific natures must be subordinated to the common and universal nature. In other words, in order to preserve nature as a whole, the individual tendencies of bodies must be subordinated to the general tendency of nature. Th roughout the wide range of cases addressed in this study, a continuity is observed in the rationales underlying the discussions about the existence of the vacuum. All of them, tacitly or not, ascribed to nature the teleological principle of subordination, mostly by interpreting traditional experimental instances. Although this continuity is clearly recognizable, variations in nuances and details are also present, owing to the various contexts within which each response to the question of the existence of a vacuum emerged.